Recycled plastic composite sheet and method of making same
Patent Information
- Application Number
- CN202510772704.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-06-11
AI Technical Summary
[0005]本发明的目的在于,提供一种塑料复合片材,解决现有再生塑料多次回收性能衰退,质量降低以及二次加工时的问题,同时克服现有再生塑料复合片材生产产品的表面不平整的问题
1、本发明选用纳米硅酸铝盐分子筛吸附再生塑料中的杂质减少性能衰退,同时增强分子链间的界面结合力,抑制二次加工时的应力开裂。呋喃/马来酰亚胺动态交联预聚体在加工过程中形成可逆网络结构,高温剪切力下动态解交联以降低熔体黏度,冷却后重新交联恢复强度。赋予片材优异的抗疲劳性和加工流动性,解决了传统再生塑料多次回收后韧性下降的问题。
Smart Images

Figure CN120682548B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of plastic composite sheet technology, specifically to recycled composite sheets prepared from recycled plastics, and also to a method for preparing recycled plastic composite sheets. Background Technology
[0002] Currently, due to the increasing consumption of flexible plastic products, the amount of discarded flexible plastic products is also increasing. To reduce resource waste, improve plastic recycling rates, and reduce pollution, governments around the world support flexible packaging suppliers in developing sustainable circular packaging materials and recycling methods, such as biodegradable / recycled plastics and the reuse of waste products, through taxation or subsidies. Currently, the former, as shown in the invention patent with publication number CN103059384A, uses masterbatch blending with recycled plastics to produce recycled plastics, but this method cannot be used for multiple recycling of recycled plastics; the latter, relying on its economic viability, has become the main method for preparing recycled plastic composite sheets.
[0003] However, traditional recycled plastics suffer from problems such as residual sulfur / nitrogen compounds and cleaning agents from secondary processing, making it difficult to eliminate residual odors. Furthermore, free radical cross-linking during secondary processing can lead to molecular chain breakage, and cross-linked foreign matter can also cause issues, limiting their application in recycled products. In addition, the free radical cross-linking of recycled plastic composite sheets can also form large molecular particles (fisheyes), which can easily result in uneven printed surfaces.
[0004] Therefore, there is an urgent need for a new type of recycled plastic composite sheet to solve the above-mentioned technical problems. Summary of the Invention
[0005] The purpose of this invention is to provide a plastic composite sheet that solves the problems of performance degradation, quality reduction, and secondary processing of existing recycled plastics after multiple recycling. At the same time, it overcomes the problem of uneven surface of products made from existing recycled plastic composite sheets.
[0006] To achieve the above objectives, the technical solution provided by the present invention is as follows: In a first aspect, the present invention provides a recycled plastic composite sheet, comprising, by weight percentage: 80-95% recycled plastic granules, 0.5-5% nano-aluminosilicate molecular sieve, 0.5-2% free radical scavenger, and 0.5-2% processing aid; The recycled plastic particles have a particle size of 50-200 μm; the processing aids include 0.1-1% of fluorinated additives and 0.1-0.3% of furan / maleimide dynamic crosslinking prepolymers, accounting for 0.1-1% of the total mass of the composite sheet; the free radical scavenger is encapsulated with NIPAM-co-AAc microspheres.
[0007] Recycled plastic granules refer to granular recycled materials made from waste plastics, such as bottles, cans, packaging bags, and industrial waste, through processes such as crushing, washing, melting, and granulation. These are often produced by high-temperature melting followed by extrusion into uniform granules using molds. Although effective in experiments, this invention still prefers to use primary recycled plastics for granulation. For secondary and higher-level recycled plastics, the performance degradation using the recycling method of this invention is slightly higher than that of primary recycled plastics (9-13%). As a preferred embodiment, the recycled plastic granules are made from materials selected from polyolefins, polyesters, etc., especially at least one of polyethylene, polypropylene, polyvinyl chloride, and polyester.
[0008] Furan / maleimide dynamically crosslinked prepolymers refer to prepolymers that can reversibly form crosslinked structures during polymer formation. Dynamic crosslinking typically refers to the ability of crosslinking points to break and recombine under specific conditions, such as temperature changes. Furan / maleimide dynamically crosslinked prepolymers contain Diels-Alder units.
[0009] Nano-aluminosilicate molecular sieves are a class of inorganic materials with regular nanoscale pore structures. They use silicon and aluminum oxide as a framework and carry balanced cation charges. In this invention, unless otherwise specified, octahedral zeolite-type molecular sieve materials are used as a preferred embodiment, and the specific surface area of the nano-aluminosilicate molecular sieve is >500 m². 2 / g. Improvements such as grafting functional groups like amino and sulfonic acid groups to enhance adsorption, and even modification methods like acid / base etching to selectively dissolve some of the framework aluminum and expand pore size, as well as other types of molecular sieve materials, are generally acceptable provided they achieve the same function and do not violate the technical concept and principles of this invention.
[0010] Free radical scavengers are chemical substances or biomolecules that can neutralize free radicals. They are often used to terminate free radical chain reactions and protect target systems from free radical damage. Optional examples include, but are not limited to, vitamin C, vitamin E, tea polyphenols, resveratrol, carotenoids, thiols, and butylated hydroxyanisole. As a preferred embodiment, the free radical scavenger is selected from hindered amines, phenolic antioxidants, and thioesters.
[0011] Fluoride additives refer to functional additives with fluorides or fluorine-containing compounds as their core components, including but not limited to sodium fluoride, calcium fluoride, aluminum fluoride, hexafluorophosphate, fluorosilicates, cryolite, etc. In this invention, the fluoride additive forms a low surface energy interface layer during processing, effectively reducing the interfacial tension between the plastic matrix and the nano-alumina silicate molecular sieve. As a preferred embodiment, the fluoride additive is selected from calcium fluoride and / or magnesium fluoride.
[0012] As a preferred embodiment, the NIPAM-co-AAc microspheres have a particle size of 1-10 μm, and the molar percentage of AAc (acrylic acid) monomer in the microsphere shell is 15-25%. The crosslinking agent is N,N'-methylenebisacrylamide. NIPAM refers to N-isopropylacrylamide. The NIPAM-co-AAc microspheres also have a high specific surface area to facilitate efficient loading of free radical scavengers.
[0013] Secondly, the present invention also provides a method for preparing a recycled plastic composite sheet having any one or more of the above-mentioned technical features, the steps of which include: S1, sorting and cleaning the recycled plastic particles, and activating the nano-aluminosilicate molecular sieve with metal ions. S2, preparation of furan / maleimide dynamic crosslinked prepolymer and free radical scavenger encapsulated in NIPAM-co-AAc microspheres; S3 uses a multi-stage mixing process to mix recycled plastic granules, nano-alumina silicate molecular sieves, free radical scavengers and processing aids, and then extrudes and granulates them. S4, hot-press stabilization treatment is applied to the raw materials and the response function of NIPAM-co-AAc microspheres is activated.
[0014] As a preferred embodiment, in S1, the sorting includes at least one of gravity sorting, infrared sorting, and electrostatic sorting; In S2, furan and maleimide react at a molar ratio of 1:1 under a protective atmosphere at 60℃±2℃ for 4 hours to obtain a prepolymer solution with a solid content of 40±5%. In S3, the mixing and granulation is carried out in three stages. In the first stage, recycled plastic particles and aluminum silicate molecular sieves are added and mixed at 75-85℃ and 500-700 rpm. In the second stage, the mixture is mixed at 95-105℃ and 700-900 rpm for 2 minutes. In the third stage, the mixture is mixed at 115-125℃ and 1100-1300 rpm for 5 minutes. In step S4, the hot-press stabilization treatment includes hot-pressing at 155-165℃ and 0.8MPa pressure for 10 minutes, followed by gradient cooling.
[0015] As a preferred embodiment, the method for preparing the NIPAM-co-AAc microspheres includes dissolving NIPAM (N-isopropylacrylamide) and AAc (acrylic acid) in a mixed solvent, pre-cooling under nitrogen protection, adding N,N'-methylenebisacrylamide to initiate polymerization, and freeze-drying to obtain porous microspheres.
[0016] As a preferred embodiment, the method for loading the NIPAM-co-AAc microspheres with the free radical scavenger includes impregnating the microspheres in a solution containing the free radical scavenger and then drying them.
[0017] The advantages and beneficial effects of this invention are as follows: 1. This invention utilizes nano-alumina silicate molecular sieves to adsorb impurities in recycled plastics, reducing performance degradation while simultaneously enhancing the interfacial bonding between molecular chains and inhibiting stress cracking during secondary processing. The furan / maleimide dynamically crosslinked prepolymer forms a reversible network structure during processing, dynamically decrosslinking under high-temperature shear stress to reduce melt viscosity, and then recrosslinking upon cooling to restore strength. This imparts excellent fatigue resistance and processing fluidity to the sheet material, solving the problem of decreased toughness after multiple recycling of traditional recycled plastics.
[0018] 2. NIPAM-co-AAc microspheres achieve on-demand release of free radical scavengers through a temperature-responsive shell. During the high-temperature processing stage, the microspheres shrink to release antioxidants, precisely inhibiting thermo-oxidative degradation; at room temperature, the microspheres seal and protect the active ingredients, extending their service life.
[0019] 3. The present invention also provides a processing method for recycled plastic composite sheets, which optimizes the dispersibility of each component by staged heating and variable speed mixing, disperses nano-molecular sieves at low temperature and medium speed to avoid agglomeration; activates dynamic cross-linked prepolymer at medium temperature and high speed; and achieves full compatibility between fluoride additives and plastic matrix at high temperature and ultra-high speed.
[0020] 4. The roller temperature gradually increases and then decreases, combined with the linear velocity gradient, to form a melt stretching-shaping equilibrium. This effectively eliminates internal stress in the sheet, reducing warping and surface ripple defects. The hot pressing combined with the gradient cooling process activates the dynamic cross-linking network recombination, while simultaneously promoting the shrinkage of the microsphere shell to release antioxidants, forming a stable sheet microstructure and resulting in a smooth finished product surface. Attached Figure Description
[0021] Figure 1 This is a process flow diagram for preparing the recycled plastic composite sheet of the present invention. Detailed Implementation
[0022] This invention provides a recycled plastic composite sheet, comprising recycled plastic particles, nano-alumina silicate molecular sieves, a free radical scavenger, and processing aids. The recycled plastic particles have a particle size of 50-200 μm; the processing aids include 0.1-1% fluorinated additives by weight of the composite sheet and 0.1-0.3% furan / maleimide dynamic crosslinked prepolymer by weight of the composite sheet. The free radical scavenger is encapsulated with NIPAM-co-AAc microspheres.
[0023] Nano-aluminosilicate molecular sieves adsorb and capture residual sulfur / nitrogen compounds and small molecule impurities in recycled plastics through their porous structure. The silicon-to-aluminum ratio (SiO2 / Al2O3, unless otherwise specified, is 5:1 in this invention) determines the cation exchange capacity, immobilizing negatively charged contaminants through ionic bonding. During the sol-gel or hydrothermal synthesis of nano-aluminosilicate molecular sieves, the hydrolysis of silicon and aluminum sources generates hydroxyl-containing intermediates (such as Si-OH and Al-OH). When the polycondensation reaction is incomplete, some hydroxyl groups remain on the surface of the framework. These surface hydroxyl groups form hydrogen bonds with the plastic molecular chains, reducing the damage to the molecular chains caused by impurities and inhibiting stress cracking during secondary processing.
[0024] As an explanation, the hydroxyl groups on the surface of nano-aluminosilicate molecular sieves may originate from the dissociation of water molecules after adsorption by the Lewis acidic sites of the aluminum-oxygen tetrahedra; the molecular sieve framework may undergo localized fracture during synthesis or post-processing, forming unsaturated Si. + Or Al 3+ The reaction of dangling bonds with water molecules; acid washing or cation exchange, etc. In addition, when the template agent is removed by high-temperature calcination of nano-alumina silicate molecular sieves, some hydroxyl groups are removed, but they are re-adsorbed with water molecules after cooling to generate hydroxyl groups. For this embodiment, the hydroxyl density can be controlled by rehydration at a specific temperature.
[0025] The molecular sieve surface is physically anchored to the plastic matrix through silicon-oxygen bonds, enhancing the interfacial bonding force between molecular chains. Simultaneously, fluorinated additives (such as CaF2 / MgF2) form a low surface energy interfacial layer during mixing, reducing melt flow resistance and promoting the uniform dispersion of the nano-molecular sieve. The furan / maleimide dynamically crosslinked prepolymer, based on the Diels-Alder reaction (DA reaction), forms a thermally reversible crosslinked network at low temperatures (<90℃) and undergoes a reverse decrosslinking reaction at high temperatures (>120℃).
[0026] As an explanation, the Diels-Alder reaction (DA reaction) is a [4+2] cycloaddition reaction that occurs between a diene and a dienophile under heating or specific conditions to form a six-membered ring structure.
[0027] The furan / maleimide dynamically crosslinked prepolymer undergoes decrosslinking during the processing of recycled plastic granules. This is partly due to reduced melt viscosity, improved flowability, and decreased fisheye defects. Another reason is the recombination of the crosslinked network during the cooling stage, restoring material strength and imparting fatigue resistance and recyclability to the sheet. Notably, microcracks generated in recycled plastics using this crosslinked prepolymer during service can be self-healed by triggering a reverse DA reaction through localized heating, releasing molecular chain segment flowability, followed by cooling and recombination of the crosslinked network.
[0028] Free radical scavengers are commonly used in plastic processing to inhibit the free radical chain reaction caused by thermo-oxidative degradation. The drawbacks of directly adding antioxidants in conventional processes include that the antioxidants start to decompose at the material mixing stage and cannot effectively protect the subsequent high-temperature molding process; unencapsulated antioxidants tend to migrate to the surface and volatilize or exude. For the antioxidants directly added in the plastic recycling process, the above-mentioned drawbacks lead to a loss rate of 30-50% in each recycling granulation, directly or indirectly resulting in a decrease in antioxidant efficiency after 3 recycling cycles of plastics. At the same time, uneven oxidation sites can cause the melt flow index (MFI) to fluctuate by up to 25%, and in addition, cause yellowing of recycled plastics, affecting the appearance of products.
[0029] The present invention overcomes the above problems by using NIPAM-co-AAc microspheres to encapsulate the free radical scavenger, and acrylic acid monomers provide hydrophilic groups to bind to the molecules of the free radical scavenger. At the processing temperature, the microsphere shell shrinks and ruptures, releasing hindered amine / phenolic antioxidants to inhibit thermo-oxidative degradation free radicals; at normal temperature, the microspheres are closed to protect the antioxidant activity. The porous structure and hydrophilic groups of the microspheres are used to achieve a high loading capacity of the antioxidants. During the hot pressing process, the temperature gradient drives the antioxidants to diffuse into the plastic matrix, forming a uniform protective layer.
[0030] The release process of the free radical scavenger dissociated from the microspheres conforms to the coupling mechanism of Fickian diffusion and shell shrinkage, which can be described by a modified Peppas equation: In the formula: M t / M ∞ is the ratio of the released amount at time t (g / g), k1 is the rate constant of the diffusion process (min -n , n is the release index, which is 0.18±0.03 in the system of the present invention), k2 is the shrinkage-dominated release coefficient (dimensionless, which is 0.82±0.05 in the system of the present invention), β is the shell shrinkage rate constant (min -1 , which is 0.25±0.02 in the system of the present invention). t is the release time (min).
[0031] When the release index n ≤ 0.43, that is, when the microspheres are intact, the free radical release rate is controlled by Fickian diffusion; when 0.43 < n < 0.85, the diffusion-swelling mechanism acts synergistically; when n ≥ 0.85, that is, after the microspheres rupture, the release of the free radical scavenger is dominated by erosion.
[0032] , in which, In the formula, δ is the shell thickness (nm, 300nm in the system of the present invention); η is the polymer viscosity (Pa·s, ≈10 at 155°C 4Pa·s). In this invention, Ea can be estimated as 45.3 kJ / mol, β0 = 2.1 × 10⁻⁶. 6 min -1 .
[0033] When k2 / k1 > 5, the free radical scavenger in the microspheres is dominated by shrinkage, and the temperature at this point can be considered the critical rupture temperature. This patent achieves 8.7 at 155℃. When βt > 3, the microspheres can be considered completely released. In this patent, βt = 2.5 after 10 minutes of hot pressing, indicating that the residual rate of the free radical scavenger is < 5%.
[0034] This invention also provides a method for preparing the above-mentioned recycled plastic sheet, which employs a multi-stage mixing process. The first stage involves low-temperature, medium-speed mixing to prevent the agglomeration of nano-molecular sieves. This temperature range softens the surface of the plastic particles but does not reach a molten state. At this point, the nano-molecular sieves preferentially adsorb onto the surface of the plastic particles through hydrogen bonds, forming a "core-shell" pre-dispersed structure. Fluoride additives then initially wet the surface of the plastic particles.
[0035] In the second stage, the dynamic crosslinking prepolymer is activated at a medium temperature and high speed. The plastic matrix reaches the melting initiation temperature, and the medium-to-high shear force causes the furan / maleimide prepolymer to deassociate into monomers, resulting in a decrease in the apparent viscosity of the melt. The DA reaction is initiated, forming primary crosslinking points with a diameter of 200-500 nm.
[0036] The third stage, high-temperature and ultra-high-speed shearing, generates a local temperature gradient, leading to the exfoliation and dispersion of the nano-molecular sieves. Simultaneously, the molten plastic matrix and additives become fully compatible. High-speed shearing also orients the molecular chains along the flow direction, and the fluorinated additives form a transition layer at the plastic / molecular sieve interface. The molecular sieves align along the shear field, creating enhanced anisotropy and improving the longitudinal strength of the sheet.
[0037] The molten melt is continuously calendered into a sheet using four rolls with gradient temperature and linear speed settings. Roll I initially melts and plasticizes the melt, eliminating agglomerates; Roll II enhances melt fluidity and initiates dynamic crosslinking; Roll III refines the phase structure at high temperature and high shear, allowing molecular chains to expand; Roll IV rapidly cools and solidifies the sheet, locking in the crosslinked network. The high-temperature section of Roll III reduces internal stress through melt stretching, while the cooling section of Roll IV (below the DA reaction temperature) promotes the recombination of the crosslinked network. Simultaneously, the high linear speed inhibits excessive crystal growth and reduces surface ripples.
[0038] The formed sheet undergoes hot-pressing stabilization to reorganize its microstructure. Hot-pressing causes partial dissociation of DA crosslinking points, rearranges molecular chain segments, and eliminates residual processing stress. Subsequent gradient cooling gradually restores the crosslinking density, forming a uniform network structure. The hot-pressing pressure promotes a microsphere rupture rate >90%, releasing antioxidants; simultaneously, fluorides migrate to the plastic / molecular sieve interface under pressure, forming a CaF2 and / or MgF2 composite layer, reducing interfacial energy and improving impact resistance. This sheet can undergo at least four recycling cycles with a tensile strength retention rate >80%, overcoming the bottleneck of the sharp performance decline of traditional recycled plastics after three cycles.
[0039] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.
[0040] Example 1 A recycled plastic composite sheet, by weight percentage, has the following composition: specific surface area 600m² 2 The composition consists of 3% nano-alumina silicate molecular sieves ( / g), 1.5% hindered amine free radical scavenger encapsulated in microspheres with a particle size of 5μm, 0.5% calcium fluoride, 0.2% furan / maleimide dynamic crosslinked prepolymer, and the balance being recycled polyethylene particles with a particle size of 150±30μm.
[0041] Its preparation method is as follows: S1: Electrostatic separation is used to remove metal impurities, and polyethylene particles are recovered by alkaline washing at 60℃.
[0042] S2: Furan and maleimide were reacted at 62°C for 4 hours under nitrogen protection in a 1:1 molar ratio to obtain a dynamic crosslinked prepolymer; the molar ratio of AAc in NIPAM-co-AAc microspheres was 20%, and the amount of crosslinking agent MBA was 2% of the total monomer mass.
[0043] S3: Multi-stage mixing, first stage: 80℃, 600rpm mixing for 10min; Second stage: Mix at 100℃ and 800rpm for 2 minutes; Third stage: Mix at 120℃ and 1200rpm for 5 minutes.
[0044] S4: The composite molded recycled plastic sheet is hot-pressed at 160℃ and 0.8MPa for 10 minutes, and then gradually cooled to room temperature.
[0045] Example 2 A recycled plastic composite sheet differs from Example 1 in that its composition has a specific surface area of 550 m². 2The composition consists of 4% nano-alumina silicate molecular sieves ( / g), 2% phenolic free radical scavenger encapsulated in microspheres with a particle size of 3μm, 0.8% magnesium fluoride, 0.3% furan / maleimide dynamic crosslinked prepolymer, and the balance being recycled polypropylene particles with a particle size of 100±20μm.
[0046] In its preparation method: In S3, the temperature in the third stage is increased to 125°C to enhance the interfacial compatibility of magnesium fluoride.
[0047] In S4, hot pressing at 165°C activates more microspheres to release antioxidants.
[0048] Example 3 A recycled plastic composite sheet differs from Example 1 in that its composition has a specific surface area of 700 m². 2 The composition consists of 2% nano-alumina silicate molecular sieves, 1% microsphere-encapsulated thioester free radical scavenger with a particle size of 10 μm, 0.6% magnesium fluoride / magnesium fluoride (1:1), 0.15% furan / maleimide dynamic crosslinked prepolymer, and the balance being recycled polyethylene terephthalate particles with a particle size of 200±20 μm.
[0049] In its preparation method: In S4, a two-step gradient cooling method is used to lock molecular orientation. Specifically, the sheet is transferred to an oven and cooled from 160°C to 120°C at a rate of 5°C / min, then cooled from 120°C to 80°C at a rate of 2°C / min. Finally, the oven is turned off and the sheet is cooled to room temperature with the oven.
[0050] Example 4 A recycled plastic composite sheet differs from Example 1 in that its composition has a specific surface area of 800 m². 2 The composition consists of 5% nano-alumina silicate molecular sieves ( / g), 1.8% microspheres encapsulated with hindered amine + phenolic free radical scavenger (8μm particle size), 1% magnesium fluoride, 0.25% furan / maleimide dynamic crosslinked prepolymer, and the balance being recycled polyethylene terephthalate particles with a particle size of 50±5μm.
[0051] In its preparation method: In S1, infrared sorting is added to remove foreign plastics.
[0052] In S2, the molar percentage of microspheres AAc reaches 25% to enhance PVC compatibility.
[0053] Example 5 A recycled plastic composite sheet differs from Example 1 in that its composition is as follows: 4% of nano-alumina silicate molecular sieve with a specific surface area of 680 m2 / g, 1.2% of microsphere-encapsulated hindered amine free radical scavenger with a particle size of 6 μm, 0.8% of sodium fluoride, 0.3% of furan / maleimide dynamic crosslinked prepolymer, and the balance being recycled polypropylene particles with a particle size of 180±20 μm.
[0054] In its preparation method: In S3: The third stage involves mixing at 1300 rpm for 6 minutes to compensate for the high surface energy of sodium fluoride.
[0055] In S4, the hot-pressing temperature is reduced to 150°C.
[0056] Example 6 A recycled plastic composite sheet, by weight percentage, comprises: 0.5% nano-alumina silicate molecular sieve with a specific surface area of 500 m² / g, 1.5% phenolic free radical scavenger encapsulated in microspheres with a particle size of 10 μm, 0.5% magnesium fluoride, 0.2% furan / maleimide dynamic crosslinked prepolymer, and the balance being recycled polyester particles with a particle size of 70 μm.
[0057] Its preparation method is as follows: S1: After removing metal impurities by electrostatic separation, the recycled polyester is treated with 10% HCl for 2 hours, followed by alkaline washing at 60°C.
[0058] Comparative Example 1 The difference from Example 1 is that no fluoride additives were added, and the gaps in the relevant materials were replaced with recycled polyethylene particles.
[0059] Comparative Example 2 The difference from Example 1 is that no nano-molecular sieve was added, and the gaps in the relevant materials were replaced with recycled polyethylene particles.
[0060] Comparative Example 3 The difference from Example 1 is that the antioxidant used is a directly added hindered amine substance, without microsphere encapsulation.
[0061] Comparative Example 4 The difference from Example 1 is that no dynamic crosslinking prepolymer was added, and polyester particles were used to replace the material gaps.
[0062] The following performance tests were performed on the above embodiments and comparative examples. Tensile strength retention rate was determined according to ISO 527-1: the ratio of the strength of the specimen to the original specimen after 5 cycles of dumbbell-shaped tensile testing at a tensile speed of 50 mm / min. Heat distortion temperature was determined according to ISO 75-1: the temperature at which the specimen, under a load of 1.8 MPa and a heating rate of 2 °C / min, bent to a deformation of 0.25 mm. Surface roughness Ra was determined according to ISO 4287 using a contact profilometer, with a sampling length of 0.8 mm and an evaluation length of 5 mm. Flatness deviation was determined according to ASTM D5947: the transverse range of the sheet was measured using a laser thickness gauge at 10 points. Yellowing index ΔYI was determined according to ASTM E313: aging test was conducted for 100 hours using a colorimeter, an aging chamber at 85 °C / 85% RH, and a D65 light source. The number of recyclable cycles refers to each cycle where the strength tested according to ISO 527 is greater than or equal to 80% of the original specimen. As shown in the table above, this invention significantly improves the overall performance of recycled plastic composite sheets through four core technologies: dynamic cross-linking network recombination, temperature-sensitive microsphere encapsulation of antioxidants, nano-molecular sieve adsorption enhancement, and fluoride interface compatibility. This overcomes the three major bottlenecks of traditional recycled plastics: performance degradation after multiple recycling cycles, severe surface defects, and low antioxidant efficiency. Examples 1-6 still meet usage requirements after four cycles. Comparative Examples 1-4, lacking fluoride, molecular sieve, microsphere encapsulated antioxidants, and dynamic cross-linking, respectively, exhibit a sharp drop in regeneration performance. This fully demonstrates that this invention, through its integrated technological innovation of dynamic network self-repair, precise controlled release of antioxidants, nano-reinforcement, and interface optimization, achieves a comprehensive improvement in the mechanical properties, heat resistance, surface quality, and cycle life of recycled plastic composite sheets.
[0063] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A recycled plastic composite sheet, characterized in that, The product comprises the following components by weight percentage: 80-95% recycled plastic granules with a particle size of 50-200 μm; 0.5-5% nano-alumina silicate molecular sieve; 0.5-2% free radical scavenger, which is encapsulated with NIPAM-co-AAc microspheres; and 0.5-2% processing aids, including 0.1-1% fluorinated additives and 0.1-0.3% furan / maleimide dynamic crosslinking prepolymer by weight percentage of the total mass of the composite sheet. The NIPAM-co-AAc microspheres have a particle size of 1-10 μm, wherein the acrylic monomer molar ratio is 15-25%, and the crosslinking agent is N,N'-methylenebisacrylamide; The preparation method of the NIPAM-co-AAc microspheres includes dissolving NIPAM and AAc in a mixed solvent, pre-cooling under a protective atmosphere, adding an initiator, and freeze-drying to obtain porous microspheres. The method for loading the NIPAM-co-AAc microspheres with the free radical scavenger includes impregnating the microspheres in a solution containing the free radical scavenger and then drying them.
2. The recycled plastic composite sheet according to claim 1, characterized in that: The recycled plastic granules are made of at least one of polyethylene, polypropylene, polyvinyl chloride, and polyester.
3. The recycled plastic composite sheet according to claim 1, characterized in that: The specific surface area of the nano-aluminosilicate molecular sieve is >500m². 2 / g.
4. The recycled plastic composite sheet according to claim 3, characterized in that: The free radical scavenger is selected from at least one of hindered amines, phenolic antioxidants, and thioesters.
5. The recycled plastic composite sheet according to claim 3, characterized in that: The fluoride additive is selected from calcium fluoride and / or magnesium fluoride.
6. The method for preparing the recycled plastic composite sheet according to any one of claims 1-5, characterized in that, Includes the following steps: S1, sorting, cleaning and recycling plastic particles and activating nano-alumina silicate molecular sieves; S2, preparation of furan / maleimide dynamic crosslinked prepolymer and free radical scavenger encapsulated in NIPAM-co-AAc microspheres; S3, mix raw materials and extrude granulation; S4 involves hot-pressing the granular raw material into sheets to activate the microsphere function.
7. The preparation method according to claim 6, characterized in that: The S1 sorting includes at least one of gravity sorting, infrared sorting, and electrostatic sorting; In S2, furan and maleimide are reacted at a molar ratio of 1:1 under a protective atmosphere at 60±2℃ for 4 hours to obtain a prepolymer solution with a solid content of 40±5%. The S3 mixing granulation process includes three stages: the first stage involves mixing recycled plastic particles and molecular sieves at 75-85℃ and 500-700rpm; the second stage involves mixing at 95-105℃ and 700-900rpm for 2 minutes; and the third stage involves mixing at 115-125℃ and 1100-1300rpm for 5 minutes. The S4 heat treatment conditions are 155-165℃, 0.8MPa hot pressing for 10 minutes followed by gradient cooling.
Citation Information
Patent Citations
Special master batch for recovering polyethylene plastic
CN103059384A
Low-viscosity reversible crosslinking R-PET regenerated material and preparation method thereof
CN117467251A
Method of encapsulating polymer additives
GB2237574A